Polyvinylamine application for functionalization of polyethylene fiber materials. Issue 4 (3rd April 2017) - Natarajan, HariharaSudan; Haase, Hajo; Mahltig, Boris
Abstract : The permanent functionalization of synthetic fibers and especially of polyethylene fibers (PE fibers) is usually difficult, because the synthetic fiber surface does not contain many functional groups for fixation of finishing agents. For this, the aim of the now presented paper is to report of a functionalization process for PE fibers using the polyelectrolyte polyvinylamine (commercially also named as Lupamin™). The polyvinylamine is applied in a HT process (HT for high temperature process using process temperatures of 95 to 140 °C) and usable to work as anchor for further applied negatively charged functionalizing agents as demonstrated in the current study with acid dyes. Also demonstrated is excellent antibacterial activity against E. coli and S. aureus by simple polyvinylamine application onto PE fibers. This reported method has a high potential for the functionalization of PE fibers and could lead in future to appropriate industrial applications using functionalized PE fibers.